2018
DOI: 10.1021/acsenergylett.7b01202
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliated 2D Lepidocrocite Titanium Oxide Nanosheets for High Sulfur Content Cathodes with Highly Stable Li–S Battery Performance

Abstract: Despite the high energy densities, lithium–sulfur (Li–S) batteries suffer from insufficient cycle life originating from the shuttling process involving lithium polysulfides (LiPSs). Various approaches have been introduced to resolve the shuttling problem, but they are not usually effective for electrodes with high sulfur contents. Here, we report an exfoliated 2D lepidocrocite titanium oxide nanosheet as a component for sulfur cathodes to suppress polysulfide dissolution markedly. In particular, the Lewis acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
64
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 42 publications
1
64
0
Order By: Relevance
“…[ 25–30 ] Therefore, a series of active materials (such as metal oxides/sulfides) with chemically polar sites were also fabricated to anchor the LiPS via the formation of the chemical bonding. [ 31–37 ] In addition to the effective immobilization of the LiPS, the rapid conversion of the intermediates on the surface of active materials with catalytic activity is also conducive to enhance the performance of Li‐S batteries. [ 38–46 ] However, the synergetic effect of chemical interaction and catalytic activity are not attracting much attention.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25–30 ] Therefore, a series of active materials (such as metal oxides/sulfides) with chemically polar sites were also fabricated to anchor the LiPS via the formation of the chemical bonding. [ 31–37 ] In addition to the effective immobilization of the LiPS, the rapid conversion of the intermediates on the surface of active materials with catalytic activity is also conducive to enhance the performance of Li‐S batteries. [ 38–46 ] However, the synergetic effect of chemical interaction and catalytic activity are not attracting much attention.…”
Section: Introductionmentioning
confidence: 99%
“…Applications of titanate nanosheets have been proposed as component in batteries [22], in heterogeneous catalysis [23], in photocatalysis [24] and as functional filler in polymer blends [25]. Recently, we have demonstrated that a film deposit of titanate nanosheet material on a glassy carbon electrode allows ferroceneboronic acid to be immobilised and binding of fructose within the nano-lamellar space to be detected [20].…”
Section: Introductionmentioning
confidence: 99%
“…Theu ltrathin structures are considered as excellent models to study the adsorption behavior of LiPSs. [7] They possess alarge electroactive surface with sufficient active sites for promoting the catalytic reactions. [8] Therefore,i ti s promising to use ultrathin structure to study the difference between the pristine surface and oxygen-vacancy-defects rich surfaces,w hich is more evident for us to gain an insightful understanding of the surface defect in catalytic reactions.I n this work, we have carried out aL ewis solid acid HNO ultrathin nanobelt for Li-S battery.…”
Section: Introductionmentioning
confidence: 99%